A review on exergy analysis of ejector refrigeration system. Issue 1 (March 2021) - Verma, Sameer Kumar; Kumar, Satyajeet; Sachdeva, Gulshan
Abstract: Owing to the human comfort, the utilization of refrigeration system has increased nowadays. In today's scenario, the air conditioning system has led to the innovative changes in the lifestyle of human beings. The Heat driven ejector refrigeration machine is a favorable alternative to a compression based refrigeration system for the point of view of minimizing energy utilization. As Exergy is directly related to the second law of thermodynamics and the system performance can be only evaluated on the basis of this thermodynamics law. On the basis of efficient performance, it has been concluded that good quality of ejector is more performance oriented rather than other components like condenser, generator and evaporator. This paper presents the idea of ejector refrigeration systems, its exergy analysis and working fluids used. It profoundly investigates the ejector technology and behaviour, exergy analysis, properties of refrigerant and its effect on the ejector refrigeration system.